2021
DOI: 10.1017/sus.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Cities and COVID-19: navigating the new normal

Abstract: Non-technical summary Urban density is erroneously regarded as the main factor in the spread of COVID-19 in cities. A review of extant literature and findings from our case study of Karachi, Pakistan indicate that inequalities in income, healthcare, and living conditions play a key role in the spread of contagions along with government responsiveness to the pandemic. Moving forward, urban policies need to address these inequalities through changes in housing policies and decentralized governance systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…There was a renewed recognition of the importance of the urban-scape to provide social experiences [23], infrastructure, and spaces to support physical and mental health [24,25], flexible and safe transport modes [26], and access to digital infrastructure [27,28] as part of basic human rights for urban living and enhanced liveability. A new definition of essential tasks [29], the importance of transportation for global and geographically remote cities such as Sydney [30], changing travel patterns [30], and the decentralisation of the urban centres driven by the drastic change in user-values and user-needs [31,32] further challenged the contemporary city centres. Limited mobility, remote working, and prioritising the health agenda became the new normal within the urban-scape, turning planning theories and our understanding of the morphology of cities upside down [20].…”
Section: Contextualising Urban Identity: the Australian Contextmentioning
confidence: 99%
“…There was a renewed recognition of the importance of the urban-scape to provide social experiences [23], infrastructure, and spaces to support physical and mental health [24,25], flexible and safe transport modes [26], and access to digital infrastructure [27,28] as part of basic human rights for urban living and enhanced liveability. A new definition of essential tasks [29], the importance of transportation for global and geographically remote cities such as Sydney [30], changing travel patterns [30], and the decentralisation of the urban centres driven by the drastic change in user-values and user-needs [31,32] further challenged the contemporary city centres. Limited mobility, remote working, and prioritising the health agenda became the new normal within the urban-scape, turning planning theories and our understanding of the morphology of cities upside down [20].…”
Section: Contextualising Urban Identity: the Australian Contextmentioning
confidence: 99%
“…Berube & Byerly-Duke (2022) observed that during the COVID-19 pandemic, the labor market has simultaneously improved and declined in various cities, but noted that the "superstar" metro areas such as New York, San Francisco, Boston, and Washington DC were on the slower end of recovery, while more affordable areas such as Atlanta, Dallas-Fort Worth, Raleigh-Durham, and Salt Lake City experienced a stronger labor market. Khan et al (2021) notes that urban density and public transit were often erroneously associated with the spread of COVID-19, causing residents to flee denser urban areas at the onset of the pandemic. The aforementioned trends suggest that the decline in office traffic in downtown areas as well as its varying effects in different cities is likely to outlast the COVID-19 pandemic, and has led to calls to reinvent downtown districts as "Central Connectivity Districts" (Florida, 2022), or to convert hollowed offices to mixed-use and recreational districts (Loh & Kim, 2021).…”
Section: Impact Of Covid-19 On Downtowns and Metropolitan Structurementioning
confidence: 99%
“…McFarlane (2021) examines the effect of urban density on the spread of Covid-19, arguing that density was conducive to the spread of the virus initially, but as the pandemic progressed, a "density-as-pathology" belief gave way to a more nuanced geographical understanding of the urban dimensions of the crisis, focusing on connections, spatial conditions, domestic overcrowding and poverty. Khan et al (2021) argue that urban density is erroneously regarded as the main factor in the spread of Covid-19 in cities, suggesting instead that the culprits include income inequality, provision of healthcare, living conditions and government responsiveness play a key role in the spread of contagion. On the other hand, Moosa and Khatatbeh (2021a) find that the infection rate depends on urban density rather than the overall population density, and that the mortality rate depends on the age structure of the population and population density rather than urban density.…”
Section: Identifying Potential Explanatory Variablesmentioning
confidence: 99%